Reddening and age of six poorly studied star clusters of the Large Magellanic Cloud derived from integrated spectra - Minniti, Javier Horacio (2014)
Aims. To increase the number of studied star clusters (SCs) of the Large Magellanic Cloud (LMC), we present flux-calibrated integrated spectra in the optical range (λ = 3700?6800 Å) for six poorly studied LMC SCs of IVA type. This type corresponds to the age range between 200 and 400 Myr. We also aim at creating a new template spectrum representative of this age range at the metallicity level of the LMC. Methods. Foreground reddening E(B − V) values and ages are derived by applying the template matching method that consists of comparing the line strengths and continuum distribution of the cluster spectra with those of template cluster spectra with known properties. The equivalent width (EW) of the Balmer lines and the diagnostic diagrams involving the sum of EWs of selected spectral lines were also employed as age indicators. Results. For the first time, we provide estimates of the clusters? reddenings and ages. As expected, all the clusters appear to be of nearly the same age, their mean value being (400 ± 100) Myr, while the resulting mean E(B − V) values range between 0.00 and 0.10 mag. Conclusions. The present cluster sample complements previous ones in an effort to gather a spectral library with several clusters per age bin. By averaging the reddening-corrected integrated spectra, weighted by their signal-to-noise ratios (S/N), a new high S/N template spectrum of 400 Myr has been created.